Class discrimination and meritocracy in the labor market: evidence from Chile - Nuñez, Javier; Gutierrez, Roberto (Estudios de Economía, 2016)
This paper studies class discrimination and meritocracy in the Chilean labor market. Employing a dataset rich in productivity and class measures, we find that upper-class professionals earn approximately 50 per cent more than those raised in lower socioeconomic backgrounds. This gap is unrelated to differences in academic performance at university, second language proficiency, postgraduate studies, schools’ academic quality, geographic origin and other standard controls, which suggests some employer discrimination. This gap is larger than gaps reported elsewhere for gender, race and physical appearance. Meritocracy is modest, as the effect of socioeconomic background on earnings outweighs that of academic performance at university.